Pengaruh Pencucian Daging Ikan Toman (Channa micropeltes) Setelah Penggaraman Terhadap Citarasa Wadi - Restu Restu (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
Wadi is one of the results of the highly favored traditional processing by Borneo people. This product is too salty, so it is necessary to find ways to reduce the salt content of wadi. Method to reduce the salt content in the fish meat is to do the washing Salting fish meat after processing is complete.This study aimed to determine the effect of fish meat after salted and washing in order to obtain the ideal flavor of wadi fish and good nutritional value. So it can be adopted by the community for the diversification of processed fishery products. Research results showed that treatment C give best result of wadi toman fish (Channa micropeltes) with nutritional value as follows: protein = 19,69%; salinity = 0,81%, Fat = 2,30%, and organoleptic value (taste) = 7.82.